B-1 Cell Heterogeneity and the Regulation of Natural and Antigen-Induced IgM Production - Baumgarth, Nicole (Frontiers in Immunology, 2016)
A small subset of B cells, termed B-1 cells, with developmental origins, phenotype and functions that are distinct from those of conventional B cells exist in mice, which contributes the vast majority of spontaneously produced “natural” IgM. Natural IgM is constitutively produced, even in the absence of microbiota, and fulfills many distinct functions in tissue-homeostasis and host-defense. B-1 cells also respond with IgM production to innate signals and pathogen exposure, while maintaining steady state levels natural IgM. Thus, within the B-1 cell pool, cells of distinct and heterogeneous functionality must exist to facilitate these different functions. This review considers three factors that may contribute to this heterogeneity: First, developmental differences regarding the origins of the precursors, second, tissue-specific signals that may differentially affect B-1 cells in the tissue compartments, and last responsiveness to self antigens as well as innate and antigen-specific signals. All three are likely to shape the repertoire and responsiveness of B-1 cells to homeostatic and antigen-induced signals and thus to contribute to the functional heterogeneity among these innate-like B cells.